Nasal and bronchial inflammation after nasal allergen challenge: assessment using noninvasive methods. (2012)
BACKGROUND Links between the upper and lower airways have been demonstrated in recent years. However, few studies have evaluated inflammation using noninvasive methods. METHODS A nasal allergen challenge was performed with pollen outside the pollen season in 30 patients with allergic rhinitis due to pollen but no asthma. Clinical and inflammatory nasal and bronchial responses to nasal allergen challenge were evaluated using the nasal symptoms score (NSS), visual analog scale (VAS), nasal geometry (volume between 2 and 5 cm [Vol2-5]) by acoustic rhinometry, lung function by spirometry, nasal nitric oxide (nNO), and exhaled nitric oxide (eNO). Values were recorded at baseline, 15 minutes, and 2 and 24 hours after challenge. Nasal lavage and exhaled breath condensate (EBC) samples were collected at 2 and 24 hours to assess 8-isoprostane, cys-leukotrienes, eosinophil cationic protein (ECP), tryptase, granulocyte-macrophage colony-stimulating factor, and interleukin (IL) 5. RESULTS NSS and VAS increased significantly at 15 minutes and 2 and 24 hours after challenge. Vol2-5 decreased significantly at 15 minutes and 2 hours, while nNO decreased at 15 minutes. All inflammatory mediators except ECP increased significantly at 2 hours in nasal lavage samples, while ECP, 8-isoprostane, and cys-leukotrienes increased at 24 hours (P < .01). In EBC, 8-isoprostane and cys-leukotrienes increased at 2 and 24 hours (P < .01). No significant changes were found at any time in lung function or eNO. CONCLUSION Nasal allergen challenge induces clinical and inflammatory responses in the nose and bronchi that can be assessed using noninvasive methods such as nasal lavage, EBC, and nNO.